True Nondisjunction of Whole Bivalents in Oocytes with Attachment and Congression Defects - Sodek, Martin; Kovacovicova, Kristina; Anger, Martin (Cytogenetic and genome research, 2017)
Chromosome segregation in mammalian oocytes is prone to errors causing aneuploidy with consequences such as precocious termination of development or severe developmental disorders. Aneuploidy also represents a serious problem in procedures utilizing mammalian gametes and early embryos in vitro. In our study, we focused on congression defects during meiosis I and observed whole nondisjoined bivalents in meiosis II as a direct consequence, together with a substantially delayed first polar body extrusion. We also show that the congression defects are accompanied by less stable attachments of the kinetochores. Our results describe a process by which congression defects directly contribute to aneuploidy.
Keywords: Animals; Female; Meiosis; mikrotubuly; segregace chromozomů; aneuploidie; ženské pohlaví; meióza; Oocytes; Time-Lapse Imaging; Nondisjunction, Genetic; kinetochory; Mice; oocyty; myši; Male; časosběrné zobrazování; Microtubules; zvířata; mužské pohlaví; konfokální mikroskopie; Aneuploidy; Chromosome Segregation; Mice, Inbred C57BL; Microscopy, Confocal; nondisjunkce genetická; Kinetochores; myši inbrední C57BL